Marketing and Post-Harvest Research (MPR) in the Philippine Fisheries: A Review of Literature - Nerissa D. Salayo (Philippine Institute for Development Studies (PIDS), 2000)
The need for efficiency in handling perishable fish and products and the overwhelming gross value added of the fishery sector are among the major reasons for the interest in marketing and post-harvest research (MPR). This paper reviewed the literature on MPR in the Philippine fishery sector from 1968 to 1999, with emphasis on the evaluation of past studies to either facilitate or respond to the needs of the industry. This review found that the number of studies on MPR started to decline after 1986, while studies on fishery resource management and conservation increased. Furthermore, MPR evolved from the fundamentals of measuring the profitability of marketing and post-harvest operations to a more intricate goal of modeling its structure, conduct and performance. In view of the need for sustainable fisheries and the increasing demand and competition arising from the call for globalization, the paper identified the research gaps and directions in MPR. Thus, a research proposal designed, at least, to underpin a segment of the identified research gaps is appended to this paper.
Keywords: 330; fisheries sector; Fischwirtschaft; Fischprodukt; Marketing; Forschung; Philippinen